Review of Leão, D.; Guerrier, O. (eds.). Figures de sages, figures de philosophes dans l'oeuvre de Plutarque (2019) (Revista Archai, 2022)
Review of Leão, D.; Guerrier, O. (eds.). Figures de sages, figures de philosophes dans l'oeuvre de Plutarque (2019)